Hierarchical microstructure constructed with graphitic carbon-coated Ni3S2 nanoparticles anchored on N-doped mesoporous carbon nanoflakes for optimized sodium storage. Issue 44 (5th November 2021) - Xu, Jia-Lin; Sun, Qiang; Chen, Hao-Jie; Yan, Wen-Jie; Lu, Pai
Abstract : A hierarchical microstructure constructed with graphitic-carbon-coated Ni3 S2 nanoparticles anchored on N-doped mesoporous carbon nanoflakes was fabricated using a nickel-based micro-nano structure as a precursor and polydopamine as a carbon source. Abstract : A hierarchical microstructure constructed with graphitic-carbon-coated Ni3 S2 nanoparticles anchored on N-doped mesoporous carbon nanoflakes was fabricated using a nickel-based micro–nano structure as a precursor and polydopamine as a carbon source. By optimizing the microstructure, the obtained Ni3 S2 /carbon composite compounded with the thickest carbon nanoflakes delivers ultrafast and stable Na-ion storage performance, and can maintain a reversible charge capacity of 372 mA h g −1 at a current density of 5 A g −1 over 250 cycles, and 316 mA h g −1 even at a current density of 20 A g −1 for 2000 cycles. These remarkable electrochemical properties can be attributed to its hierarchical microstructure of graphitic-carbon-coated Ni3 S2 particles and N-doped mesoporous carbon nanoflakes, which provide easy accessibility to the electrolyte, fast electron transport and Na + diffusion, and even relieve the strain caused by the volume expansion upon cycling.